1995
DOI: 10.1046/j.1365-313x.1995.07010049.x
|View full text |Cite
|
Sign up to set email alerts
|

The gene for the major cuticular wax‐associated protein and three homologous genes from broccoli (Brassica oleracea) and their expression patterns

Abstract: The gene for the major protein (WAX9) found in surface wax of broccoli, designated wax9D, and three homologous genes (wax9A, B and C) were isolated from a genomic library using the previously isolated cDNA encoding the WAX9 protein as the probe; all four genes were sequenced. Genomic Southern blot analysis using the WAX9 cDNA as a probe showed the presence of at least four homologous genes in broccoli genome. The sequence of the originally isolated WAX9 cDNA matched with that of gene D. All four genes have an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
63
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 0 publications
1
63
0
Order By: Relevance
“…The observation of expression of the 1346-GUS construct in young cells of the germinating root led us to examine further the expression pattern in the germinating seedling, since both our previous data (Fleming et al, 1992) and those of other groups (Skriver et al, 1992;Kotilainen et al, 1994;Pyee and Kolattukudy, 1995) suggested that LTP gene expression is restricted to aerial portions of the plant. However, examples in which an LTP protein (Thoma et al, 1993) or ltp transcripts (Molina and García-Olmedo, 1993; Krause et al, 1994) are found in roots are known.…”
Section: The Nfltpl Cene 1s Specifically Regulated During Cerminationmentioning
confidence: 95%
See 1 more Smart Citation
“…The observation of expression of the 1346-GUS construct in young cells of the germinating root led us to examine further the expression pattern in the germinating seedling, since both our previous data (Fleming et al, 1992) and those of other groups (Skriver et al, 1992;Kotilainen et al, 1994;Pyee and Kolattukudy, 1995) suggested that LTP gene expression is restricted to aerial portions of the plant. However, examples in which an LTP protein (Thoma et al, 1993) or ltp transcripts (Molina and García-Olmedo, 1993; Krause et al, 1994) are found in roots are known.…”
Section: The Nfltpl Cene 1s Specifically Regulated During Cerminationmentioning
confidence: 95%
“…In situ hybridizations have shown accumulation of Itp transcripts in epidermal layers of tobacco (Fleming et al, 1992), tomato (Fleming et al, 1993), and Arabidopsis (Thoma et al, 1994), and anti-LTP antibodies recognized epitopes in cell walls and intercellular spaces in Arabidopsis (Thoma et al, 1993). Furthermore, in broccoli, LTP is the most abundant protein in the extracellular wax (Pyee andKolattukudy, 1994, 1995). Such a specific localization of LTP in the epidermal cell wall is incompatible with a role in general lipid redistribution, and, in the light of a11 these observations, LTPs have been proposed to play a role in the transport of extracellular lipophilic material.…”
mentioning
confidence: 99%
“…Plant LTPs are small (7-10 kD), abundant, and basic proteins that have a hydrophobic pocket capable of accommodating fatty acids or lysophospholipid molecules (Shin et al, 1995;Beisson et al, 2003). The results of plant genome and EST projects have demonstrated the presence of multiple LTP isoforms, which are speculated to be associated with diverse functions including cutin and wax assembly, pathogen defense, antifreezing, long-distance signaling, and cell wall loosening (Pyee and Kolattukudy, 1995;Molina and García-Olmedo, 1997;Maldonado et al, 2002;Beisson et al, 2003;Jeroen et al, 2005;Cameron et al, 2006;Roy-Barman et al, 2006;Choi et al, 2008). Most plant LTPs localize to the cell wall, which suggests that LTPs play a role in cutin monomers and wax transport (Pyee and Kolattukudy, 1995).…”
mentioning
confidence: 99%
“…The results of plant genome and EST projects have demonstrated the presence of multiple LTP isoforms, which are speculated to be associated with diverse functions including cutin and wax assembly, pathogen defense, antifreezing, long-distance signaling, and cell wall loosening (Pyee and Kolattukudy, 1995;Molina and García-Olmedo, 1997;Maldonado et al, 2002;Beisson et al, 2003;Jeroen et al, 2005;Cameron et al, 2006;Roy-Barman et al, 2006;Choi et al, 2008). Most plant LTPs localize to the cell wall, which suggests that LTPs play a role in cutin monomers and wax transport (Pyee and Kolattukudy, 1995). The accumulation of cuticular wax on the leaves of tree tobacco (Nicotiana glauca) and the concomitant increase in LTP expression in response to drought stress indirectly suggest that LTP is involved in the accumulation of wax (Cameron et al, 2006).…”
mentioning
confidence: 99%
“…Although this purified fraction showed only one band in a silver-stained SDS-PAGE gel, it contained more than one homologous polypeptide, as revealed by protein sequencing (Hincha et al 2001). All peptides belong to the family of WAX9 proteins (Pyee et al 1994;Pyee & Kolattukudy 1995), which show a high degree of sequence homology to plant LTPs (figure 4). WAX9 E, purified from the wax layer of cabbage leaves, has lipid transfer activity between liposomal membranes but no cryoprotective activity.…”
Section: (D ) Lectins As Cryoprotective Model Proteinsmentioning
confidence: 97%